A cross-sectional study of diseases prevailing in an orthopaedic OPD at a tertiary care hospital in the Mumbai metropolitan region - Rathod, Girish; Borole, Pushkar; Shetty, Chandan; Raut, Nitin; Britto, Namrata; Gawali, Vijaykumar (International Journal of Research in Orthopaedics, 2022)
Background: The orthopaedic out-patient department of a tertiary care hospital plays a crucial role in the health care system as it attends to a large number of patients. The goal of the study is to observe the etiological patterns of common issues that prevail in an Orthopaedics OPD of a hectic tertiary care hospital, which could in turn help to understand the distribution of illnesses in a particular geographical area. Methods: Analysis of 1605 patient records was carried out from the period July 2020 to December 2020, to assess the orthopaedic out-patient load and prevailing diseases. Initial medical records of the patients were analyzed and the data collected were subjected to statistical analysis using IBM SPSS software version 1.0. Results: The primary diagnosis of patients visiting the orthopaedic OPD during the Covid-19 period are observed to be as follows: acute and chronic back ache (27.29%), arthritis (26.23%), joint stiffness (10.03%), ligamentous sprains (9.84%), neck-related problem (6.92), tendinopathies and enthesopathies (6.60%), non-specific body aches (5.11%), post-operative follow-up (4.05%),bone fractures (2.37%), soft tissue injuries (0.93%), and neuropathies (0.62%). Conclusions: The study presenting the overview of diseases prevailing in an orthopaedic OPD in a tertiary care center could help in formulating better prevention and treatment strategies to overcome such medical conditions irrespective of the presence of a pandemic.